Hypercapsule is the cornerstone of Klebsiella pneumoniae in inducing pyogenic liver abscess - Hu, Dakang; Chen, Wenjie; Wang, Weiwen; Tian, Dongxing; Fu, Pan; Ren, Ping; Mu, Qing; Li, Gang; Jiang, Xiaofei (Frontiers in Cellular and Infection Microbiology, 2023)
Purpose To investigate the mechanisms of Klebsiella pneumoniae-induced pyogenic liver abscess (PLA). Methods Forty-three K. pneumoniae strains from PLAs and 436 from non-PLAs were collected. Their differences were compared for virulence genes and factors, sequence types, and serotypes. Virulence genes wzi, wzy-K1, and wzi+wzy-K1 were deleted in K. pneumoniae NTUH-K2044. Various analyses, such as transmission electron microscopy, neutrophil killing tests, and mouse lethality tests, were used to confirm the consequent changes. Results Differences were found between K. pneumoniae strains from PLA and non-PLA samples for virulence genes and factors, including metabolism genes (allS and peg-344), capsular polysaccharide (CPS)-synthesis channel gene (wzy-K1), CPS-regulating genes (p-rmpA, p-rmpA2, and c-rmpA), and siderophore genes (iucA and iroN). When wzy-K1 was positive, the difference between PLA and non-PLA samples was only observed with c-rmpA. Δwzi, Δwzy-K1, and ΔwziΔwzy-K1 strains reverted to hypovirulence. In the Kupffer cell stimulation assay, interleukin (IL)-6, IL-12, IL-10, and transforming growth factor-β secretions were found to be equivalent in NTUH-K2044, Δwzi, Δwzy-K1, and ΔwziΔwzy-K1 groups. Lower IL-1β and higher tumor necrosis factor-α secretions were observed for Δwzi, Δwzy-K1, and ΔwziΔwzy-K1. Conclusions Hypercapsule production is the cornerstone of hypervirulence, regardless of exopolysaccharides. K1 K. pneumoniae-induced PLA may decrease core inflammatory cytokines rather than increase anti-inflammatory cytokines. Exopolysaccharides could also attenuate the inflammatory response to aid in the immune escape of K. pneumoniae.